Implications of the New EU Carbon Border Tax for the EAEU - M. M. Murashko (Проблемы постсоветского пространства)
The article focuses on the interaction of the European Union and the Eurasian Economic Union in the context of green technological transformation. The European Union is actively pursuing a policy of transition to a carbon-neutral economy. In this regard, it intends to implement a special tax mechanism, which may significantly limit export opportunities for the EAEU. Moreover, the EU is one of the key partners of the EAEU and plays a major role in the economic development of individual countries that are members of the integration association. The article further discusses the projected risks for the EAEU member states, and provides measures that can ensure trade security of the Union’s countries on the European markets. In particular, measures should be aimed at the development own environmental legislation, harmonization of the legislation of EAEU member states, and the creation of permanent negotiation mechanisms to bring together the positions of EAEU countries in the context of the climate policy pursued by the European Union.